Understanding of Values in M. Scheler’s Ethics - Anilionytė, Loreta (Problemos, 1995)
M. Scheler’s conception of values is considered in the paper. M. Scheler is said to have modified E. Husserl’s ideas viewing values as objective phenomena, accessible via a priori evidence. The essence of the phenomena is said to have no link with subjects and no influence upon their knowing, and to be indifferent to reality. However, according the author of the paper, this leads M. Scheler’s conception to some difficulties in the specification of values.